DETERMINING AND MAINTAINING THE AMOUNT OF PROFITABILITY OF NET WORKING ASSETS - Јелена Пољашевић (Acta Economica, 2011)
Net working assets are an important indicator of a company’s liquidity. To determine the optimal amount, the management has to know that over‐investing into net working assets can lead to a decline in the company’s profitability, but on the other hand, net working assets insufficiency ultimately leads to the company’s insolvency. Managing net working assets involves calculating optimal amounts of cash and short‐term placements; stocks and claims on one side and finding adequate financing sources for the working capital on the other. This paper analyzes financial reports from the companies in the official Banjaluka stock market to determine the relation of net working assets and profitability, and tries to find a connection between these two variables. As it is always emphasized in literature, the amount of net working assets is foremostly bound to the company’s field of work and then to some other factors, such as the market placement, terms of sale and its business cycle. Research has shown that, if we exclude the companies with a negative return rate during the whole period of observation, the amount of net working assets did not significantly affect the rate of return on its capital.